A Study Of Desk Information System Utilization Among Manufacture Managers: A Case Of Selected Companies In Bukit Kayu Hitam, Kedah - Yahmed, Zakarya A. J. (2008)
The general purpose of this study was to find out whether a relationship between perceived case of use, perceived usefulness and utilization of DIS. This study was determining the review of literature about technology acceptance model as the underpinning theory to the theoretical framework. This study proposes the perceived credibility as a construct to enhance the understanding of an individual's acceptance behavior of utilization of DIS in manufacture context. Another additional construct is the internet self efficacy that also plays the important role in the usage of utilization of DIS in manufacture in Bukit Kayu Hitam of Kedah. Multivariate analysis was conducted to examine the perceived ease of use and perceive usefulness to the implementation of desktop information system among manufacture managers. The study confirmed that managers should improve their utilization level in desktop information system in order to improve the performance their company.